PD-1 Is an Immune-Inflammatory Potential Biomarker in Cerebrospinal Fluid and Serum of Intractable Epilepsy - Tang, Hong; Wang, Xuefeng (BioMed research international, 2021)
Purpose. Previous studies have demonstrated that immune and inflammatory factors play an important role in recurrent seizures. The PD-1-PD-L pathway plays a central and peripheral immunosuppressive role by regulating multiple signaling pathways during the inflammatory and immunologic processes. This study is aimed at assessing PD-1 levels in cerebrospinal fluid (CSF) and serum samples from patients with intractable epilepsy. Methods. PD-1 levels were assessed in CSF and serum samples from 67 patients with intractable epilepsy (41 and 26 individuals with partial seizure and intractable status epilepticus, respectively) and 25 healthy controls, using flow cytometric analysis and sandwich enzyme-linked immunosorbent assays (ELISA). Results. Serum-PD-1+CD4+CD25high Treg levels in the experimental groups and the control group were 10.26±2.53 (PS group), 35.95±27.51 (ISE group), and 4.69±2.44 (control group). In addition, CSF-PD-1 level in patients with epilepsy was higher than that in the control group (50.45±29.56 versus 19.37±4.51), indicating a statistically significant difference (P<0.05). Interestingly, serum- and CSF-PD-1 levels in individuals with epilepsy were not affected by antiepileptic drug and treatment course, but by epilepsy onset level. Of note, the increase of CSF- and serum-PD-1 levels was more pronounced in subjects with intractable status epilepticus than those with partial seizure. Conclusion. Serum- and CSF-PD-1 levels constitute a potential clinical diagnostic biomarker for intractable epilepsy and could also be used for differential diagnosis.